Ethics In Business Law: A Paternalistic Legal Philosophy Approach From John Stuart Mill - Suputra, I Dewa Gde Ery; Kurniawan, I Gede Agus; Gorda, Anak Agung Ayu Ngurah Sri Rahayu (SASI, 2025)
Introduction: In the modern business world, John Stuart Mill's paternalistic legal philosophy, especially the "harm" principle, is very relevant to balance market freedom and protection of public interests, such as consumers, workers, and the environment, through regulations aimed at reducing the negative impacts of business activities.Purposes of the Research: The purpose of this study is to analyze the application of John Stuart Mill's paternalistic principles in business law and to evaluate the relevance of Mill's legal philosophy to modern business regulation.Methods of the Research: This study uses normative legal methods to analyze the application of John Stuart Mill's paternalistic principles in business law, with conceptual, legislative, and case approaches, and utilizing primary, secondary, and tertiary legal materials analyzed qualitatively and deductively.Results Main Findings of the Research: John Stuart Mill’s paternalistic principles, particularly the harm principle, are highly relevant in modern business regulation as they balance market freedom with protection of the public interest, as seen in consumer protection, employment, corporate social responsibility (CSR), and environmental regulations, which aim to protect consumers, workers, and ecosystems. Despite challenges such as resistance from business actors, the application of this principle remains essential to ensure that freedom in business does not harm society and the environment, and supports sustainability and public welfare.